Web 2.0 in learning English: the student perspective - Kufi, Elmaziye Ozguer; Ozgur, Birikim (Elsevier Science Bv, 2009)
Although literature is rich in discussions on technology integration in the learning process, very few studies elaborate on the effectiveness of the most recent web-based tools from the student perspective. As the target audience to benefit from the use of web-based tools is learners, their perceptions play a significant role in their successful implementation. Based on this rationale, the present study aimed to develop a comprehensive insight into two hundred freshman students' perceptions regarding the use of an interactive web environment in English communication courses offered by the department of General Education at Eastern Mediterranean University. The study made use of a mixed method approach and the participants' perceptions were elicited through the use of a questionnaire which included open-ended questions to collect qualitative data and also structured questions which required the collection of quantitative data. Responses given to open-ended questions were analyzed through coding the statements and responses to structured questions were analyzed by calculating the frequencies. The analysis of data shows that the majority of students is positive about the use of an interactive web environment and find its use beneficial for their learning. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: Web 2.0; web based tools; interactive web environments; constructivism; learning english; english language teaching